STRATEGI PEMERINTAH DESA DALAM MENINGKATKAN KUALITAS PEMUDA MELALUI KEBUDAYAAN DI DESA TAMBAH ASRI KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - lestari, umi fitriana (DEMOKRASI, 2024)
This study aims to examine and analyze the village government's strategy in improving the quality of youth through culture in Tambah Asri Village, Tugumulyo District, Musi Rawas Regency. The focus of this study is based on the theory put forward by Bintoro Tjokroamidjojo (2017), namely: Determination of objectives, Policy formulation and Operationalization.The study uses a qualitative method with a qualitative descriptive approach through observation, interview and documentation. The types of data sources used are primary data and secondary data. Using data analysis techniques, data reduction, data presentation and drawing conclusions. The informants of this study consisted of village officials, art team coaches and art youth.The results of this study indicate that formulating goal determination must take into account strengths such as direction, motivation that arouses and profitable opportunities and also weaknesses such as challenges and risks. The village government sets a routine practice schedule and participates in art events to support the creativity of village youth in improving the quality of youth to be more responsive to things that smell of art in order to preserve Indonesian culture. The village government sets a vision and mission that becomes a reference for the youth arts team to improve and develop culture among the community. The youth arts always appear at important village events such as the commemoration of August 17, welcoming guests and earth alms. The village government acts as a supporting factor that is willing to provide facilities and infrastructure for the arts team. The youth who are members of the arts team act as an external factor that supports the village government in realizing the achievement of improving the quality of village youth in the field of dance arts culture.Â Keywords: Strategy, Village Government, Youth, Culture